The Hidden Costs of Choice in the Labor Market - Pak Hung Au; King King Li; Qing Zhang; Rong Zhu (Institute of Labor Economics (IZA), 2023)
Freedom of choice is often thought to improve efficiency. We experimentally investigate the effect of giving workers a choice between compensation schemes with and without a CSR component (CSR/NoCSR) on labor market participation decision and work performance, compared to the alternative of exogenous assignment. Classical economic theory suggests that giving workers a choice should not reduce their performance. Our results show that there are hidden costs associated with the right of choice. When a worker is allowed to choose his or her compensation scheme, the labor market participation rate is significantly lower than when the same scheme is exogenously assigned. Work quality is also significantly lower for those who choose CSR, as well as for those who choose no CSR, than for those who are exogenously assigned to the same scheme.We propose a model of signaling with image concerns to explain why the freedom of choice may induce reduced participation and effort exertion of workers.
Keywords: M14; J01; C9; M52; 330; choice; signaling; image concerns; corporate social responsibility; labor; experiment